The spatial agglomeration of museums, a case study in London. Issue 2 (15th March 2017) - Zhang, Hongmei; Xu, Feifei; Lu, Lin; Yu, Peng
ABSTRACT: Museums play a significant role in urban revival and the tourism development of cities. As part of the cultural industry, the spatial agglomeration of museums becomes important. However, it is an under-researched area. This research uses a combined method of Herfindahl index and Gini Coefficient to analyze the influence of four categories of factors (demand factors, traffic factors, labor cost factors and facilities factors) on the spatial distribution of museums. It uses London as a case study, discussing the spatial distribution and agglomeration of the museums in Greater London. The results prove that a museum agglomeration in Greater London does exist, which is in a distribution of a circular pattern with the city center at the core, meanwhile influenced by the Thames River. It also shows a certain degree of linear distribution of the agglomeration. The results suggest that among the four categories of influencing factors, the demand factors are the robust elements that affect museums' spatial distribution, which is different from manufacturing and productive services industries. Implications for practice are drawn out.